Pengaruh Pengandalian Persediaan Just In Time Terhadap Efisiensi pengadaan Persediaan Bahan Baku - Efrianti, Desi (Institut Bisnis dan Informatika Kesatuan, 2014)
Inventory control of raw materials is an important element in a company. At this point inventory control of raw materials needed, which should always be available in the warehouse of raw materials for the production needs, but in order to maintain efficiency, raw materials also should not be too much available in warehouse. if the raw materials are available in warehouse too much will increase the cost of a few elements. The purpose of this study was to observe and investigate how the selection method of inventory control (JIT Method) can affect the efficiency of the procurement of raw materials to a company. The results showed that the CV Jawara Karsa Agusto has not implemented any inventory control methods to manage raw material inventory. There are some changes in expenditure on procurement of raw materials when the author tries to apply the method of JIT inventory control. Evaluation results of this research show that the application of the JIT done, there is the addition of the efficiency of the procurement of raw materials amounting to Rp 366,245,280